Fatwa Ulama NU (Nahdlatul Ulama) Dan Muhammadiyah Jawa Timur Tentang Hisab Rukyat - Miftahul Ulum (STAI Syaichona Moh. Cholil Bangkalan, 2015)
This research is descriptive-comparative trying to depict a comprehensive and in-depth analysis of astronomy to the views of figures NU (NU) and Muhammadiyah East Java related to the beginning of the month Qamariyah determination, particularly in determining the beginning of the month of Shawwal, the approach to astronomy. It was a tradition that during the holy month of Ramadan will enter Indonesian Muslims as if back â€˜disputeâ€™ about when to start the 1st of Ramadan which is the initial implementation of fasting obligatory for all Muslims. At least three times we Muslims are frequently â€˜conflictingâ€™ namely in the determination of one Ramadan, Shawwal 1 and 10 Dzulhijah, during the Eid al-Adha. There are two methods for determining the initial months of Hijrah, ie rukyat method (observation) and reckoning (calculation). Literally, rukyat means â€˜lookâ€™. The most common meaning is â€œseen with the naked eyeâ€. So, in general, rukyat can be said as the observation of the new moon in accordance with the Sunnah of the Prophet. Instead, reckoning comes from the Arabic â€œhabasaâ€ means counting, thinking and counting. In the discipline of astronomy, said reckoning have the meaning arithmetical position of celestial objects. This study seeks to remind Muslims about the timing of the start and end of Ramadhan, especially in 2006-2007 in which NU and Muhammadiyah as the largest Islamic organization in Indonesia establishes a different policy. In the case of the very significant differences between the two organizations that need to be studied to be withdrawn so that the threads and sought a solution to the unification / similarities in determining the beginning of the month in question. In essence, according to NU that we are required to fast during Ramadan from the beginning to the end of the fasting month with an initial determination by method: Ruâ€™yah al-Hilal, or through seeing the new moon (months) both Ramadhan and Syawal. If ruâ€™yat month of Ramadhan has been set then obliged to fast. If ru'yat Shawwal has been established, it shall not fast (iftar). In contrast, since 1969, no longer do rukyat Muhammadiyah and choose to use a form of al-hilal reckoning, this is because rukyatul hilal or see the new moon directly is a very difficult job and paradigms that Islam is a religion that does not narrow, the solution can be used reckoning as a determinant of the beginning of the Muslim lunar month. Broadly speaking, the view of East Java NU figures concerning the determination of the start of the month Qamariyah is with ruyah al-hilal, otherwise the leaders of Muhammadiyah East Java build ontologies criteria for determining the beginning of the month Qamariyah with arithmetic. In addressing the criteria difference between NU and Muhammadiyah, the majority leader of East Java NU to follow the government, others respond with following the instructions Executive Board of the NU.